Diclofenac as an environmental threat: Impact on the photosynthetic processes of Lemna minor chloroplasts. (June 2019) - Hájková, Markéta; Kummerová, Marie; Zezulka, Štěpán; Babula, Petr; Váczi, Peter
Abstract: Mechanisms of pharmaceuticals action on biochemical and physiological processes in plants that determine plant growth and development are still mostly unknown. This study deals with the effects of non-steroidal anti-inflammatory drug diclofenac (DCF) on photosynthesis as an essential anabolic process. Changes in primary and secondary photosynthetic processes were assessed in chloroplasts isolated from Lemna minor exposed to 1, 10, 100, and 1000 μM DCF. Decreases in the potential and effective quantum yields of photosystem II (FV /FM by 21%, ΦII by 44% compared to control), changes in non-photochemical fluorescence quenching (NPQ), and a substantial drop in Hill reaction activity (by 73%), especially under 1000 μM DCF, were found. Limitation of electron transport through photosystem II was confirmed by increased fluorescence signals in steps J and I (by 50% and 23%, respectively, under 1000 μM DCF) in OJIP fluorescence transient. Photosystem I exhibited changes only in the redox state of P700 reaction centres (decrease in Pm by 10%, increase in reduced P700 by 5% under 1000 μM DCF). Similarly, RuBisCO activity was only lowered by 30% under 1000 μM DCF. In contrast, a significant increase in reactive oxygen and nitrogen species (by 116% and 157%, respectively) was observed under 10 μM DCF, and lipid peroxidation increased even at 1 μM DCF (by nearly seven times compared to the control). Results demonstrate the ability of environmentally relevant DCF concentrations to induce oxidative stress in isolated duckweed chloroplasts; however, photosynthetic processes were affected considerably only by the highest DCF treatments. Graphical abstract: Image 103817 Highlights: Photosystem II and RuBisCO activity are affected only by high diclofenac treatments. Hill reaction activity is more sensitive to DCF than thylakoid electron transport. Direct effects of diclofenac on photosystem I are negligible. Diclofenac-induced increases in reactive oxygen and nitrogen species in chloroplasts.